Emotional Attachment dan Pengaruhnya terhadap Perilaku Digital Hoarding pada Generasi Z - Vanessa Brilliancy La Tossa; Vania Ardelia (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Digital hoarding has become an increasingly relevant psychological phenomenon in the digital era, particularly among Generation Z, who are highly engaged with digital devices and online storage. The tendency to accumulate digital files may be influenced by emotional attachment to personal digital objects such as photos, videos, documents, messages, and other meaningful files. This study aimed to examine the effect of emotional attachment on digital hoarding behavior among Generation Z. A quantitative cross-sectional survey design was employed. The participants consisted of 255 Generation Z respondents selected using purposive sampling based on their active use of digital devices and habit of storing digital files. Data were collected using the Digital Hoarding Questionnaire (DHQ) to measure digital hoarding behavior and the Emotional Attachment Scale (EAS) to assess emotional attachment. Both instruments demonstrated satisfactory reliability, with Cronbach’s alpha coefficients of 0.802 for the DHQ and 0.858 for the EAS. Data were analyzed using simple linear regression after the assumptions of normality and linearity were fulfilled. The results showed that emotional attachment had a significant effect on digital hoarding behavior (F = 215.6, p < 0.001). The coefficient of determination indicated that emotional attachment contributed 46% to digital hoarding behavior (RÂ² = 0.460), while the remaining 54% was influenced by other factors outside this study. Additional gender-based analysis showed that male respondents had slightly higher mean scores for both emotional attachment and digital hoarding than female respondents, although the difference was not significant. These findings indicate that emotional attachment is an important psychological factor underlying digital hoarding among Generation Z. The study provides practical implications for digital well-being education, particularly in encouraging digital decluttering, file organization, and healthier emotional regulation toward digital possessions.